ANALISIS PRODUKTIVITAS DAN PENDAPATAN USAHATANI DI KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - B01111087, Diko (Jurnal Pembangunan dan Pemerataan, 2016)
The title of this research is â€œThe Analysis of Productivity and Income ofPineapple Farm in Sungai Raya Regency of Kubu Rayaâ€. This research is aimedto determine the average of production and farm income pineapple in SungaiRaya Regency of Kubu Raya. This research is used qualitative descriptivemethod by using questionnaires and interviews which is addressed to therespondent and informant.The result showed thath the average production of pineapple farm in theDistrict od Sungai Raya was relatively low. This is caused by the use of PGR(Plant Growt Regulator) which are not evenly distributed on each pineapplefarmers due to lack of knowledge on the goods that farmers will make farmersare afraid to make use it. PGR (Plant Growth Regulator) indicates that farmproductivity pineapple in Sungai Raya Regency of Kubu Raya was low whilefamerâ€™s income is based on calculations showed the considerable result whichmeans the result of cultivation of pineapple provides the high benefitsKeyword : Productivity, Net Income, Plan Growth Regulator